Climate, fire and vegetation history from subtropical North Stradbroke Island (Minjerribah), eastern Australia, during the last three interglacials. (9th August 2021) - Kemp, Christopher; Tibby, John; Barr, Cameron; Arnold, Lee
ABSTRACT: Records of Australian palaeoclimate beyond the last glacial cycle are rare, limiting detailed analysis of long‐term climate trends and associated ecosystem responses. This study analyses a discontinuous pollen and charcoal record from Fern Gully Lagoon, North Stradbroke Island (Minjerribah), subtropical Queensland, Australia, which covers much of the last 210 , 000 years. Climate variation is inferred from changes in vegetation, while analysis of micro‐ and macrocharcoal is used to infer fire activity. Pollen assemblages consist of 40% rainforest taxa during marine isotope stage (MIS) 7a–c and early MIS 5. These are inferred to result from high rainfall in the Australian subtropics, which was also evident in north‐east and central Australia. Human impact from 21 , 000 years ago likely supressed post‐MIS 2 rainforest expansion to some extent. However, the increased Holocene abundance of herbs and grasses and reduced representation of aquatic taxa suggest that the Holocene was relatively dry when compared with early MIS 5 and MIS 7a–c. Similar MIS 5 and early MIS 7a–c climates, in contrast to a notably drier Holocene, suggest that the progressive interglacial drying trend most strongly recorded in central Australia was not a major feature of subtropical eastern Australian climates.